Dispatching and Scheduling of the Lock Chamber of Three Gorges Lock. Issue 1 (October 2020) - Qiangqiang, Qi; Yu, Zhang; Shuo, Zhang
Abstract: In order to maximize the navigation capacity of the Three Gorges and relieve the backlog of vessels, considering the regulation of navigation and the attributes of vessels of Three Gorges Hub, the concept of priority ship collection is introduced and the priority of dispatching is determined. Taking the utilization ratio of lock chamber and the mean latency of vessels at lockage as optimization target, an optimal scheduling algorithm for Three Gorge Lock chamber scheduling is proposed, which integrates two-dimensional strip packing heuristic algorithm and genetic algorithm. The proposed algorithm is tested on the vessels downlink data of Three Gorges Lock in August 2016 then compared with the manual arrangement strategy. The results show that the proposed algorithm has better performance in utilization ratio of lock chamber and the mean latency of vessels at lockage. The proposed algorithm can improve the carrying capacity of the Three Gorges ship lock to a certain extent.